Histone Demethylase RBP2 Is Critical for Breast Cancer Progression and Metastasis - Jian Cao; Zongzhi Liu; William K.C. Cheung; Minghui Zhao; Sophia Y. Chen; Siew Wee Chan; Carmen J. Booth; Don X. Nguyen; Qin Yan (Cell Reports, 2014)
Metastasis is a major clinical challenge for cancer treatment. Emerging evidence suggests that aberrant epigenetic modifications contribute significantly to tumor formation and progression. However, the drivers and roles of such epigenetic changes in tumor metastasis are still poorly understood. Using bioinformatic analysis of human breast cancer gene-expression data sets, we identified histone demethylase RBP2 as a putative mediator of metastatic progression. By using both human breast cancer cells and genetically engineered mice, we demonstrated that RBP2 is critical for breast cancer metastasis to the lung in multiple in vivo models. Mechanistically, RBP2 promotes metastasis as a pleiotropic positive regulator of many metastasis genes, including TNC. In addition, RBP2 loss suppresses tumor formation in MMTV-neu transgenic mice. These results suggest that therapeutic targeting of RBP2 is a potential strategy for inhibition of tumor progression and metastasis.